Owning Maine’s Future: Fostering a Cooperative Economy in Maine - Taylor, Davis; Brown, Rob (Maine Policy Review, 2017)
Maine’s economy faces a host of well-known challenges: reliance on natural resource extraction or low-quality service jobs, geographic isolation, challenging climate, and out-migration, especially of young adults. Staying on this course is undesirable, but traditional economic development fixes have had limited success. The authors examine the possibilities of making cooperatively owned businesses a central feature of Maine’s economy. They outline the characteristics, benefits, and challenges of cooperatives and identify six important sectors of the Maine economy in which cooperative ownership already plays an important role or could make more contributions to economic and community vitality. The authors describe several other regions, with a focus on Finland, with strong cooperative economies or businesses, and examine the socioeconomic benefits and institutional features that encourage the development of cooperatives. The article concludes with policy recommendations that could facilitate similar outcomes in Maine.
Keywords: Maine; co-ops; worker-owned businesses; consumer cooperatives; business cooperatives; multistakeholder cooperatives